Isolation of saprophytic basidiomycetes from soil - Harris, David, author; Thorn, R. Greg, author; Reddy, C. Adinarayana, author; Paul, Eldor A., author; American Society for Microbiology, publisher (Colorado State University. Libraries, 1996)
A method with the combined advantages of soil particle washing, selective inhibitors, and an indicator substrate was developed to isolate saprophytic basidiomycetes from soil. Organic particles were washed from soil and plated on a medium containing lignin, guaiacol, and benomyl, which reduced mold growth and allowed detection of basidiomycetes producing laccase or peroxidase. The 64 soil samples yielded 67 basidiomycete isolates, representing 51 groups on the basis of morphology and physiology. This method should facilitate investigations into the biodiversity of soil basidiomycetes and yield organisms that are useful in bioremediation of soils contaminated with pesticides or other recalcitrant aromatic compounds.
Publisher version: https://aem.asm.org/content/62/11/4288.abstract.
Keywords: soil organic matter; carbon cycling; plant residue fraction; soil structure; fertility